2020
DOI: 10.35808/ersj/1623
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Perspective on Ambidexterity, Creativity and Networking: Literature Overview

Abstract: Purpose: This paper is aimed at investigating the research trends about ambidexterity blended with creativity and checking whether networking could be one of the approaches making that perspective more comprehensive. Approach/Methodology/Design: Almost every industry, characterized by particular specifics provides different managerial pressures. Those tensions are the drivers of changing managerial cognition aimed at finding the balance between improving the organizational performance and value creating. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…The results of this study are in line with the past literature, which has shown that PLB promotes ambidexterity among employees and enhances their level of innovation as well as creativity (Radomska & Wo1czek, 2020;Yi et al, 2019;Zhaohui, 2018). A leader's opening and closing behaviors affect employees' behavior because these behaviors not only allow the employee to work by taking advantage of previous experiences but also motivate them and increase their participation in the discovery of new ideas.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study are in line with the past literature, which has shown that PLB promotes ambidexterity among employees and enhances their level of innovation as well as creativity (Radomska & Wo1czek, 2020;Yi et al, 2019;Zhaohui, 2018). A leader's opening and closing behaviors affect employees' behavior because these behaviors not only allow the employee to work by taking advantage of previous experiences but also motivate them and increase their participation in the discovery of new ideas.…”
Section: Discussionsupporting
confidence: 91%
“…According to researchers, explorative and exploitative behavior promote innovation among employees (Canie¨ls & Veld, 2019;Rosing & Zacher, 2017). Exploration focuses on thinking outside the box, engaging in experiments, and looking for new ways of doing things that altogether increase creativity (Radomska & Wo1czek, 2020). On the other hand, exploitation involves risk avoidance and rules following, encouraging employees to display creativity.…”
Section: Mediating Role Of Employee Exploration and Employee Exploita...mentioning
confidence: 99%
See 1 more Smart Citation
“…Radomska and Wołczek ( 2020 ) analyzed 62 previous studies on the relationship between ambidexterity and creativity in an organization. Their finding is as follows: (i) there are four research perspectives on ambidexterity and creativity issue, namely learning process and knowledge acquiring, organizational context, managerial practice, and company's characteristic; (ii) creativity belongs to the managerial practice, which is a dominant perspective compared to the other three perspectives; (iii) to enhance creativity in an organization, we need to facilitate Team Ambidexterity to embrace the right approach.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Enhancing creativity is perceived as a challenge in finding the balance between the two aspects of Ambidexterity (Jones and Casulli, 2014 ; Radomska and Wołczek, 2020 ). However, finding this balance requires an ambidexterity-based approach (Lubatkin et al, 2006 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%